A Proposal to Organize and Promote Replications - Coffman, Lucas C.; Niederle, Muriel; Wilson, Alistair J. (American Economic Review, 2017)
We make a two-pronged proposal to (i) strengthen the incentives for replication work and (ii) better organize and draw attention to the replications that are conducted. First we propose that top journals publish short “replication reports.” These reports could summarize novel work replicating an existing high-impact paper, or they could highlight a replication result embedded in a wider-scope published paper. Second, we suggest incentivizing replications with the currency of our profession: citations. Enforcing a norm of citing replication work alongside the original would provide incentives for replications to both authors and journals.